Europe crawls towards low-carbon transport - Dings, J (Oxford Institute for Energy Studies, 2017)
On the back of the Paris climate deal and record high global temperatures, Europe is slowly crawling towards a 2030 low-carbon strategy for transport. Later this year the European Commission is supposed to present a strategy paper, followed by concrete policy initiatives over the next year or so. This article looks into what Europe has done so far in the context of 2020 initiatives and what the key lessons are for the forthcoming action with timeline 2030.